Algae as nutritional and functional food sources: revisiting our understanding - Mark L. Wells; Philippe Potin; James S. Craigie; John A. Raven; Sabeeha S. Merchant; Katherine E. Helliwell; Alison G. Smith; Mary Ellen Camire; Susan H. Brawley (Journal of Applied Phycology, 2017)

Heterophil/Lymphocyte Alterations as a Measure of Stress in American Alligators in Relation to Anthropogenic Disturbance in a Louisiana Intermediate Marsh - Christopher Murray; Justin Rheubert; Michael Easter; Mark Merchant; Brian Crother (Journal of Marine Science and Engineering, 2015)
Numerous anthropogenic factors represent environmental threats to Gulf Coast wetland ecosystems and associated fauna. American alligators (Alligator mississippiensis) have been subject to long-term management and used as ecological and physiological indicators of habitat quality in response to anthropogenic events and stochastic natural disasters. The present study monitored heterophil to lymphocyte ratios (an indicator of stress), in American alligators in a Louisiana intermediate marsh from 2009 to 2011, a time period that coincides with an oil inundation event that occurred in 2011. Sixteen alligators were observed and processed morphometrically (total length, snout-vent length and body mass). Heterophil to lymphocyte ratios were negatively correlated with size, suggesting larger American alligators were physiologically more resilient to the disturbance, more able to actively avoid these poor conditions, or are less affected by localized disturbance.

Phylogenomic analysis of the Chlamydomonas genome unmasks proteins potentially involved in photosynthetic function and regulation - Arthur R. Grossman; Steven J. Karpowicz; Mark Heinnickel; David Dewez; Blaise Hamel; Rachel Dent; Krishna K. Niyogi; Xenie Johnson; Jean Alric; Francis-André Wollman; Huiying Li; Sabeeha S. Merchant (Photosynthesis Research, 2010)

Quercitol links the physiology, taxonomy and evolution of 279 eucalypt species - Andrew Merchant; Pauline Y. Ladiges; Mark A. Adams (Global Ecology and Biogeography, 2007)
Aim Increasing aridity over geological time‐scales has driven a high degree of speciation within the Eucalyptus group in Australia. Isolation of gene pools by climatic and edaphic conditions and high rates of out‐crossing have given rise to a large diversity of adaptive traits. Among these traits, adaptations of cellular biochemistry are likely to be significant in preserving cellular function during arid conditions. The aim of this study was to determine the quantitative and qualitative distribution of soluble carbohydrates and polyols in Eucalyptus . Location Australia. Methods We sampled 279 of the 700+ documented eucalypts (in the three genera comprising the eucalypts: Angophora Cav., Corymbia Hill & Johnson and Eucalyptus L’Hér.) and analysed leaf tissues for the occurrence of low‐molecular‐weight carbohydrates and polyols. Results We have uncovered a discrete pattern in concentration of quercitol (a cyclitol) that correlates strongly with the current taxonomic classification based on both morphology and DNA sequencing. We also uncovered a further and stronger correlation between the presence of quercitol in leaf tissues and a reduced growth (mallee) form. Main conclusions These findings, together with the chemical properties of quercitol, suggest that we have uncovered a chemical marker of structural adaptations to arid conditions, thus providing a putative, broad‐scale functional link to adaptation to aridity.